The absence of JC virus antigens in Indian children with medulloblastomas - Vasishta Rakesh; Pasricha Neelam; Nath Avindra; Sehgal Shobha (Wolters Kluwer Medknow Publications, 2009)
Background: The human polyoma virus, also known as the JC virus (JCV), replicates predominantly in the oligodendrocytes, the myelin producing cells in the central nervous system and results in the fatal demyelinating disease progressive multifocal leukoencephalopathy (PML) especially in immunosuppressed patients with AIDS. Several investigators have also documented the presence of the viral genome and early and late antigens in a variety of brain tumors particularly in medulloblastomas, gliomas and ependymomas. Reports also indicate the presence of JCV in patients with colon cancer. The T antigen of JCV has been postulated to have oncogenic potential as substantiated by animal experiments. Although JCV infects 80% of the population, there are scant epidemiological studies regarding JCV from India. There are also reports of the low prevalence of PML in patients with AIDS from India and Africa. Aim: This study was undertaken to investigate if Indian children with medulloblastomas also show evidence of JCV. Methods: Twenty-two consecutive cases of medulloblastomas were investigated for the presence of T antigen and agnoprotein of JCV in biopsy specimens by immunohistochemistry. Antibodies to the agnoprotein antigen raised in rabbits and a monoclonal antibody against SV40 T antigen raised in mice that cross-reacts with JCV T antigen were used. Results: Out of 22 patients, 4 had desmoplastic tumors while the rest had classical tumors. All children were below the age of 10. Results indicate that while PML tissues showed consistent immunostaining both with antibody to T antigen and agnoprotein antibody, none of the tumors showed any positive staining for JC viral antigens. Conclusion: JCV antigens could not be detected by immunohistochemistry in the tumor tissues of Indian children with medulloblastomas.